Carbon nanosheet high-efficiency hydrogen evolution catalytic material loaded with RuCo alloy nanoparticles through in-situ growth on carbon nanofibers

By growing carbon nanosheet catalytic materials with RuCo alloy nanoparticles in situ on carbon nanofibers, the problems of high reaction overpotential and high cost of precious metals during the electrolytic hydrogen production process are solved, and high efficiency hydrogen evolution reaction is achieved and production costs are reduced.

CN119243225APending Publication Date: 2025-01-03ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411139722.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the reaction during the electrolytic hydrogen production process requires excessive overpotentials, slow kinetics, and high cost of precious metal catalysts, making it difficult to achieve large-scale application, and the catalytic activity of transition metals is limited.

Method used

High-efficiency hydrogen evolution catalytic materials of carbon nanosheets supported by RuCo alloy nanoparticles are grown in situ on carbon nanofibers. They are prepared by electrospinning, immersion and carbonization technology, combined with ZIF-L derivatized materials, reduce the use of precious metals and improve catalytic activity.

Benefits of technology

In alkaline electrolytes, the overpotential is significantly reduced, the hydrogen evolution reaction efficiency is improved, and it has excellent catalytic activity and stability. It can work continuously for 100 hours, and the voltage drop is small, which reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243225A_ABST
    Figure CN119243225A_ABST
Patent Text Reader

Abstract

The invention discloses a high-efficiency hydrogen evolution catalytic material for carbon nanosheets loaded with RuCo alloy nanoparticles through in-situ growth on carbon nanofibers, which is characterized in that nanofibers prepared by an electrostatic spinning technology are used as a substrate, and ruthenium-doped ZIF-L nanosheets are grown on the nanofibers in situ by combining a soaking method; and after carbonization, RuCo alloy nanoparticles formed by high-temperature decomposition are uniformly dispersed on the ZIF-L derived carbon nanosheets. The catalytic performance of the prepared catalytic material is greatly improved, the usage amount of precious metal can be reduced, the production cost is reduced, meanwhile, excellent HER catalytic activity in alkaline electrolyte is achieved, and good stability and durability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic material production, and in particular to a carbon nanosheet high-efficiency hydrogen evolution catalytic material with in-situ growth of RuCo alloy nanoparticles loaded on carbon nanofibers. Background Art

[0002] Energy shortage and environmental pollution are becoming increasingly serious, so the development of clean and renewable energy has become a focus of social attention. Hydrogen energy, as a sustainable, clean and safe energy source, has the potential to meet both environmental and energy needs. Among the many hydrogen production processes, compared with traditional hydrogen production methods, water electrolysis is a clean, by-product-free, efficient and high-purity hydrogen production method. However, due to the influence of factors such as solution resistance and electrode resistance in the process of water electrolysis, the reaction requires too high an overpotential and has slow kinetics. Therefore, efficient catalysts are needed to reduce the reaction energy barrier and enhance the catalytic reaction to improve the efficiency of the hydrogen evolution reaction (HER).

[0003] Precious metals such as Pt, Ru and Ir have excellent catalytic activity, and Pt-based materials have been widely regarded as benchmark catalysts for HER, but their high cost and scarcity prevent them from being widely used. Transition metals are abundant and cheap, but their catalytic activity is limited due to their own limitations. Therefore, it is of utmost importance to rationally modify them and develop a catalytic material with low price and excellent catalytic performance.

[0004] As a homologue of Pt, Ru has a suitable hydrogen binding strength, thus having a high water dissociation efficiency and excellent catalytic performance. And compared with Pt, Ru also has certain economic advantages, and its price is significantly lower than Pt. Therefore, it is considered to be an important component for constructing efficient alkaline hydrogen evolution reaction electrocatalysts. Metal organic framework (MOF) is a porous material with a periodic topological structure formed by metal ions (or metal clusters) and organic ligands through coordination bonds. Its unique porous structure and large specific surface area contribute to the catalytic activity of HER, making it a special template and precursor for HER catalysts. Combining the monomer metal MOF with precious metals with good catalytic activity (such as Pt, Ru, Ir) to prepare MOF-derived materials can reduce the content of precious metals and reduce production costs while ensuring good catalytic activity and stability. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon nanosheet with in-situ growth and loading of RuCo alloy nanoparticles on carbon nanofibers. The carbon nanosheet has an efficient hydrogen evolution catalytic material, which can reduce the use of precious metals and reduce production costs, and has excellent HER catalytic activity in alkaline electrolytes, as well as good stability and durability.

[0006] The technical solution adopted by the present invention to solve its technical problem is: A carbon nanosheet high-efficiency hydrogen evolution catalytic material with in-situ growth of RuCo alloy nanoparticles on carbon nanofibers is prepared by the following steps: Step 1: Preparation of precursor cobalt nanofibers by electrospinning: Adding cobalt acetate and polyacrylonitrile to N,N-dimethylformamide and stirring thoroughly to obtain a uniformly mixed precursor solution; then transferring the precursor solution to a syringe for electrospinning to prepare precursor cobalt nanofibers; In order to obtain an efficient hydrogen evolution catalytic material with carbon nanosheets loaded with RuCo alloy nanoparticles in situ grown on carbon nanofibers with good catalytic effect, ruthenium chloride and cobalt acetate cannot be added together to the precursor solution to form precursor ruthenium cobalt nanofibers; if cobalt acetate and ruthenium chloride are added together to the precursor solution for spinning, part of the nanoparticles obtained by pyrolysis will be exposed on the surface of the fiber, and part will be wrapped inside by the carbon layer of the carbon fiber. After that, the carbon nanosheets grown in situ on the fiber will also cover the alloy nanoparticles formed on the fiber surface, hindering the exposure of active sites.

[0007] Step 2: Soak: A 2-methylimidazole aqueous solution, a cobalt nitrate aqueous solution and a ruthenium chloride aqueous solution are prepared respectively, the precursor cobalt nanofiber is immersed in the 2-methylimidazole aqueous solution for ultrasonic treatment and then taken out, and then the 2-methylimidazole aqueous solution, the cobalt nitrate aqueous solution and the ruthenium chloride aqueous solution are mixed to obtain a mixed immersion solution, and then the ultrasonically treated precursor cobalt nanofiber is immersed in the mixed immersion solution, taken out for cleaning, and dried to obtain an in-situ growth ruthenium-doped ZIF-L nanosheet intermediate on the nanofiber; The reason why cobalt acetate is used in step 1 spinning is that the effect of spinning is taken into consideration. Spinning with cobalt acetate will be smoother, while using cobalt nitrate will produce droplets during spinning, and the outlet of the syringe is not very stable. Therefore, cobalt acetate is used to prepare the spinning solution precursor. In step 2, cobalt nitrate can better form ZIF with 2-methylimidazole in the immersion.

[0008] During the immersion process, the metal ions (cobalt) coordinate with the organic ligands (2-methylimidazole). Therefore, after the immersion and coordination are completed, sheet-like ZIF-L grows in situ on the nanofibers.

[0009] The present invention does not soak in 2-methylimidazole for a long time, but only performs a simple ultrasonic treatment to allow the nanofibers to more fully contact the soaking solution, so that nanosheets can be better grown in situ on the fiber surface during the subsequent soaking process.

[0010] Step 3: Carbonization: The ruthenium-doped ZIF-L nanosheet intermediate in situ grown on the nanofibers prepared above is first pre-oxidized in a constant temperature forced air drying oven, and then placed in a tubular furnace for calcination. Argon is introduced as a protective gas during the heating process, and finally an efficient hydrogen evolution catalytic material of carbon nanosheets loaded with RuCo alloy nanoparticles in situ grown on carbon nanofibers is obtained.

[0011] During the soaking process of the present invention, Ru-doped ZIF nanosheets are in-situ grown on the nanofibers, and after high-temperature carbonization, the nanofibers are converted into carbon nanofibers, and the ZIF nanosheets are converted into carbon nanosheets, that is, the morphology of the nanosheets in-situ grown on the fibers does not change, but the RuCo alloy nanoparticles formed during the high-temperature carbonization process are uniformly dispersed on the carbon nanosheets converted from ZIF.

[0012] The present invention uses nanofibers prepared by electrospinning technology as a substrate, and in situ grows ruthenium-doped ZIF-L nanosheets on the nanofibers in combination with an immersion method, and the RuCo alloy nanoparticles formed by high-temperature decomposition after carbonization are uniformly dispersed on the carbon nanosheets derived from ZIF-L. The ruthenium-doped ZIF-L nanosheets are obtained by in-situ growth on the nanofibers by immersion, and the RuCo alloy formed after high-temperature carbonization will be uniformly dispersed on the carbon nanosheets. The catalytic performance of the catalytic material prepared by the present invention is greatly improved. On the one hand, this is because the unique microstructure of the in-situ growth of nanosheets on the nanofibers can load more metal content, while preventing the aggregation of the formed nanoparticles, and can expose more active sites; on the other hand, the alloying of ruthenium and cobalt can effectively reduce the reaction energy barrier and improve the hydrogen evolution efficiency, thereby having excellent catalytic activity.

[0013] The present invention adopts a simple electrospinning, soaking and carbonization strategy to prepare the catalytic material. The operation process is simple and easy, and the unique micromorphology and alloying constructed make the final catalytic material have excellent HER catalytic activity.

[0014] At present, many catalytic materials cannot maintain good stability and durability while maintaining excellent catalytic performance. On the one hand, it may be because the defects of the material itself make it unable to maintain long-term stability. On the other hand, it may be because the preparation of the working electrode uses a binder, which reduces the stability. The catalytic material prepared by the present invention is tested for stability. The results show that it can maintain good catalytic activity while maintaining good stability. On the one hand, the surface of the main active site of the catalytic material prepared by the present invention is wrapped with a thin carbon layer (attached Figure 3), while maintaining good catalytic activity, it can prevent the nanoparticles from being dissolved during the reaction, inhibit the loss of active substances, and ensure the stability of the catalytic material; on the other hand, the present invention prepares a self-supporting electrocatalyst, which can be directly used as a working electrode without adding Nafion, polytetrafluoroethylene and other binders to ensure the adhesion between the catalyst and the electrode to prepare the working electrode. The use of these binders will lead to problems such as decreased conductivity and blocked active sites ( J. Mater. Chem. A , 2017,5, 12027-12033;Chemical EngineeringJournal. 2020;397:125481;Journal of Alloys and Compounds.2022;911:165094.), which leads to the problem of decreased stability. The carbon nanofibers prepared by the electrospinning technology of the present invention have good conductivity and can be used as a self-supporting working electrode, which helps to improve the stability of the catalytic material.

[0015] In step 1, the raw material ratio of the precursor solution is: 1-3 mM cobalt acetate, 1-3 g polyacrylonitrile, and 10-15 mL N,N-dimethylformamide.

[0016] In step 1, the electrospinning parameters were: temperature of 30 ± 5 °C, voltage of 20-25 KV, flow rate of 0.5-0.7 mL / h, and the distance between the needle and the receiver was 15-20 cm.

[0017] In step 2, the concentration of the 2-methylimidazole aqueous solution is 0.3-0.5 mmoL / mL, the concentration of the cobalt nitrate aqueous solution is 0.05-0.1 mmoL / mL, and the concentration of the ruthenium chloride aqueous solution is 0.1-0.2 mmoL / mL.

[0018] In step 2, the molar ratio of 2-methylimidazole: cobalt nitrate: ruthenium chloride is 32:4:1.

[0019] In step 2, the precursor cobalt nanofibers are immersed in the mixed immersion solution for 30-90 minutes.

[0020] In step three, the pre-oxidation temperature is controlled at 200±50℃ and the time is controlled at 3-5 hours. The pre-oxidation process is to introduce functional groups such as hydroxyl and carbonyl into the fiber molecules. These functional groups can form hydrogen bonds between and within molecules, thereby enhancing the structural stability of the fiber, making the fiber harder and stronger, and able to maintain a certain toughness after subsequent high-temperature carbonization, and not easy to break brittlely.

[0021] In step three, the calcination process is divided into three stages: the first stage: heating from room temperature to 300±50℃, the heating rate is 4-6℃ / min, and the insulation time is 1-3 minutes; the second stage: heating from 300±50℃ to 900±100℃, the heating rate is 4-6℃ / min, and the insulation time is 2-3 hours; the third stage: naturally cooling to room temperature.

[0022] The beneficial effects of the present invention are: 1. The carbon nanofiber prepared by the present invention is in situ grown on the carbon nanofiber and loaded with RuCo alloy nanoparticles and carbon nanosheets. In the alkaline medium of 1M KOH, the catalytic material has a high efficiency of hydrogen evolution at 10 mA / cm 2 Only 78 mV overpotential is required at current density of 100 mA / cm 2 Only 228 mV overpotential is required at a current density of 100 mA / cm 2 After working continuously for 100 hours at a current density of , the voltage only dropped by 102 mV, showing good stability.

[0023] 2. The present invention uses a trace amount of precious metals to ensure the catalytic performance of the catalytic material, and at the same time uses non-precious metals with abundant reserves and low prices in the raw materials to reduce the use of precious metals and reduce production costs. In addition, the preparation method is a simple electrospinning, soaking and carbonization process, which is simple to operate, and the catalytic material finally obtained has excellent catalytic performance and stability. It can be seen that the catalytic material prepared by the present invention has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The invention discloses an X-ray diffraction (XRD) test spectrum of a carbon nanosheet high-efficiency hydrogen evolution catalytic material prepared by the present invention, which is a carbon nanofiber on which RuCo alloy nanoparticles are in-situ grown and loaded.

[0025] Figure 2 The present invention is a scanning electron microscope (SEM) image of a carbon nanosheet high-efficiency hydrogen evolution catalytic material prepared by the present invention, which is in-situ grown on a carbon nanofiber and loaded with RuCo alloy nanoparticles.

[0026] Figure 3 This is a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image of a carbon nanosheet high-efficiency hydrogen evolution catalytic material prepared by the present invention, which is in situ grown on a carbon nanofiber and loaded with RuCo alloy nanoparticles.

[0027] Figure 4 The present invention discloses an LSV comparison curve and a stability test curve corresponding to the HER of a carbon nanosheet high-efficiency hydrogen evolution catalytic material prepared by the present invention and in situ grown on carbon nanofibers and loaded with RuCo alloy nanoparticles in a 1 M KOH alkaline environment.

[0028] Figure 5 This is a photograph of the hydrogen evolution catalytic material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described in detail below through specific embodiments.

[0030] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.

[0031] Ruthenium chloride, 2-methylimidazole, cobalt acetate tetrahydrate, N,N-dimethylformamide and polyacrylonitrile were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; cobalt nitrate hexahydrate was purchased from Shanghai MacLean Biotechnology Co., Ltd.

[0032] Range 3: 2-methylimidazole aqueous solution concentration is 6-10mmoL / L, cobalt nitrate aqueous solution concentration is 1-2mmoL / L, ruthenium chloride aqueous solution concentration is 0.1-0.3mmoL / L Embodiment 1: The first step is electrospinning: weigh 1.5 g PAN (polyacrylonitrile), 2 mM C4H6CoO 4• 4H2O (cobalt acetate tetrahydrate) was dissolved in 11 g N,N-dimethylformamide solution and stirred to obtain a uniformly mixed precursor solution. The precursor solution was transferred to a 10 mL syringe for electrospinning at a voltage of 22 KV, a spinning speed of 0.6 mL / h, a distance between the needle and the receiver of 18 cm, and a temperature of 32 °C to prepare precursor cobalt nanofibers.

[0033] The second step is to soak the solution: 0.65 g 2-methylimidazole is dissolved in 20 mL deionized water as solution A, 0.29 g Co (NO3) 2• 6H2O (cobalt nitrate hexahydrate) was dissolved in 20 mL of deionized water to obtain solution B, 0.207 g RuCl3 (ruthenium chloride) was dissolved in 10 mL of deionized water to obtain solution C, the prepared precursor nanofibers were ultrasonically treated in solution A for 2 min, and according to the molar ratio of 2-methylimidazole: cobalt nitrate: ruthenium chloride of 32:4:1, solution B and solution C were added to solution A to form a uniform immersion solution D, and the ultrasonically treated nanofibers were immersed in solution D for 1 hour, and finally taken out, washed, and dried.

[0034] The third step is carbonization treatment. The intermediate nanofibers prepared above are pre-oxidized at 230°C for 4 hours, and then transferred to a tube furnace for high-temperature carbonization. The carbonization program is set as follows: the first stage: heating to 300°C, the heating rate is 5°C / min, and the holding time is 1 minute; the second stage: heating from 300°C to 900°C, the heating rate is 5°C / min, and the holding time is 3 hours; the third stage: naturally cool to room temperature. Argon is introduced as a protective gas throughout the carbonization process.

[0035] Embodiment 2: The first step is electrospinning: weigh 1.5 g PAN (polyacrylonitrile), 2 mM C4H6CoO 4• 4H2O (cobalt acetate tetrahydrate) was dissolved in 11 g N,N-dimethylformamide solution and stirred to obtain a uniformly mixed precursor solution. The precursor solution was transferred to a 10 mL syringe for electrospinning at a voltage of 22 KV, a spinning speed of 0.6 mL / h, a distance between the needle and the receiver of 18 cm, and a temperature of 32 °C to prepare precursor cobalt nanofibers.

[0036] The second step is to soak the solution: 0.65 g 2-methylimidazole is dissolved in 20 mL deionized water as solution A, 0.29 g Co (NO3) 2• 6H2O (cobalt nitrate hexahydrate) was dissolved in 20 mL of deionized water to obtain solution B, 0.207 g RuCl3 (ruthenium chloride) was dissolved in 10 mL of deionized water to obtain solution C, the prepared precursor nanofibers were ultrasonically treated in solution A for 2 min, and according to the molar ratio of 2-methylimidazole: cobalt nitrate: ruthenium chloride of 32:4:1, solution B and solution C were added to solution A to form a uniform immersion solution D, and the ultrasonically treated nanofibers were immersed in solution D for 90 min, and finally taken out, washed, and dried.

[0037] The third step is carbonization treatment. The intermediate nanofibers prepared above are pre-oxidized at 230°C for 4 hours, and then transferred to a tube furnace for high-temperature carbonization. The carbonization program is set as follows: the first stage: heating to 250°C, the heating rate is 4°C / min, and the heat preservation time is 3 minutes; the second stage: heating to 800°C, the heating rate is 4°C / min, and the heat preservation time is 3 hours; the third stage: naturally cool to room temperature. Argon is introduced as a protective gas throughout the carbonization process.

[0038] Embodiment 3: The first step is electrospinning: weigh 1.5 g PAN (polyacrylonitrile), 2 mM C4H6CoO 4•4H2O (cobalt acetate tetrahydrate) was dissolved in 11 g N,N-dimethylformamide solution and stirred to obtain a uniformly mixed precursor solution. The precursor solution was transferred to a 10 mL syringe for electrospinning at a voltage of 22 KV, a spinning speed of 0.6 mL / h, a distance between the needle and the receiver of 18 cm, and a temperature of 32 °C to prepare precursor cobalt nanofibers.

[0039] The second step is to soak the solution: 0.65 g 2-methylimidazole is dissolved in 20 mL deionized water as solution A, 0.29 g Co (NO3) 2• 6H2O (cobalt nitrate hexahydrate) was dissolved in 20 mL of deionized water to obtain solution B, 0.207 g of RuCl3 (ruthenium chloride) was dissolved in 10 g of deionized water to obtain solution C, the prepared precursor nanofibers were ultrasonically treated in solution A for 2 min, and according to the molar ratio of 2-methylimidazole: cobalt nitrate: ruthenium chloride of 32:4:1, solution B and solution C were added to solution A to form a uniform immersion solution D, and the ultrasonically treated nanofibers were immersed in solution D for 30 min, and finally taken out, washed, and dried.

[0040] The third step is carbonization treatment. The intermediate nanofibers prepared above are pre-oxidized at 230°C for 4 hours, and then transferred to a tube furnace for high-temperature carbonization. The carbonization program is set as follows: the first stage: heating to 350°C, the heating rate is 5°C / min, and the heat preservation time is 2 minutes; the second stage: heating to 1000°C, the heating rate is 5°C / min, and the heat preservation time is 2 hours; the third stage: naturally cool to room temperature. Argon is introduced as a protective gas throughout the carbonization process.

[0041] Embodiment 4: The difference between this embodiment and embodiment 1 is that the electrospinning parameters in the first step are: temperature of 25° C., voltage of 20 KV, spinning speed of 0.5 mL / h, and distance between the needle and the receiver of 15 cm. Other parameters are the same as those in embodiment 1.

[0042] Embodiment 5: The difference between this embodiment and embodiment 1 is that the electrospinning parameters in the first step are: temperature of 35° C., voltage of 25 KV, spinning speed of 0.7 mL / h, and distance between the needle and the receiver of 20 cm. Other parameters are the same as those in embodiment 1.

[0043] Embodiment 6: The difference between this embodiment and embodiment 1 is that: In the first step: weigh 1 g PAN (polyacrylonitrile), 1 mM C4H6CoO 4•4H2O (cobalt acetate tetrahydrate) was dissolved in 10 mL of N,N-dimethylformamide solution. Other steps were the same as those in Example 1.

[0044] Embodiment 7: The difference between this embodiment and embodiment 1 is that: In the first step: weigh 3 g PAN (polyacrylonitrile), 3 mM C4H6CoO 4• 4H2O (cobalt acetate tetrahydrate) was dissolved in 15 mL of N,N-dimethylformamide solution. Other steps were the same as those in Example 1.

[0045] Embodiment 8: The difference between this embodiment and embodiment 1 is that: In the third step: the pre-oxidation temperature is controlled at 150°C and the time is controlled at 5 hours. The heating rate set in the carbonization program is 6°C / min. Others are the same as in Example 1.

[0046] Embodiment 9: The difference between this embodiment and embodiment 1 is that: In the third step: the pre-oxidation temperature is controlled at 250°C and the time is controlled at 3 hours. Other steps are the same as in Example 1.

[0047] In step 2, the concentration of the 2-methylimidazole aqueous solution is 0.3-0.5 mmoL / mL, the concentration of the cobalt nitrate aqueous solution is 0.05-0.1 mmoL / mL, and the concentration of the ruthenium chloride aqueous solution is 0.1-0.2 mmoL / mL.

[0048] Embodiment 10: The difference between this embodiment and embodiment 1 is that: In the second step: weigh 0.49 g 2-methylimidazole in 20 mL deionized water as solution A, 0.29 g Co (NO3) 2• 6H2O (cobalt nitrate hexahydrate) was dissolved in 20 mL of deionized water to obtain solution B, and 0.207 g of RuCl3 (ruthenium chloride) was dissolved in 10 mL of deionized water to obtain solution C. Other steps were the same as those in Example 1.

[0049] Embodiment 11: The difference between this embodiment and embodiment 1 is that: In the second step: weigh 0.82 g 2-methylimidazole in 20 mL deionized water as solution A, 0.58 g Co (NO3) 2• 6H2O (cobalt nitrate hexahydrate) was dissolved in 20 mL of deionized water to obtain solution B, and 0.207 g of RuCl3 (ruthenium chloride) was dissolved in 5 mL of deionized water to obtain solution C. Other steps were the same as those in Example 1.

[0050] Comparative Example 1: This example is different from Example 1 in that there is no pre-oxidation.

[0051] Comparative Example 1 does not perform pre-oxidation, and the prepared catalytic material has poor structural stability, poor toughness, and is brittle ( Figure 5 ), cannot be used as a self-supporting working electrode, and relevant performance tests cannot be performed.

[0052] Figure 1 This is an X-ray diffraction (XRD) test spectrum of the catalytic material prepared in Example 1 of the present invention. Figure 1 The diffraction peak at 26.22° in the XRD is the carbon peak, which corresponds to the carbon nanofibers formed after high-temperature carbonization. The following three diffraction peaks correspond to metallic cobalt, but it can be seen that the diffraction peak of metallic cobalt of Co / CNFs is shifted to a low angle compared with that of Co / CNFs, proving that the RuCo alloy was successfully synthesized.

[0053] Figure 2 This is a scanning electron microscope (SEM) characterization image of the catalytic material prepared in Example 1 of the present invention. From the image, it can be clearly observed that carbon nanosheets are in-situ grown on the carbon nanofibers, and the formed nanoparticles are evenly distributed on the carbon nanosheets. Figure 2 a and Figure 2 b is the scanning electron microscope image at different magnifications. Figure 2 b Scanning image at a smaller magnification shows the structure of nanosheets generated in situ on carbon nanofibers, and Figure 2 The larger magnification scan in a can more clearly show the dispersed nanoparticles formed on the nanosheets.

[0054] Figure 3 This is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) characterization image of the catalytic material prepared in Example 1 of the present invention. In the transmission image, it can be further seen that triangular nanosheets are in situ grown on the carbon nanofibers and the structure of nanoparticles is evenly distributed on the nanosheets, and the lattice fringes of the catalytic material can be observed. Figure 3 The transmission electron microscope image a clearly shows the structure of the formed nanosheets, and the nanoparticles dispersed on the nanosheets can be more clearly observed. Figure 3 b The carbon layer on the surface of the nanoparticles is marked in the transmission image. The thinner carbon layer can protect the nanoparticles during the reaction while ensuring good catalytic activity. Figure 3 The lattice fringe diagram in c shows that the interplanar spacing of the prepared catalytic material is 0.241 nm, corresponding to the (111) crystal plane.

[0055] Figure 4The LSV curve diagram and stability test curve of the hydrogen evolution reaction (HER) of the catalytic material prepared in Example 1 of the present invention in an alkaline electrolyte (1 M KOH) show that the catalytic material has excellent catalytic activity and stability in an alkaline environment. Figure 4 The CNFs in the first figure are samples prepared by the electrospinning technology in Example 1 without adding metal salts and only adding polyacrylonitrile (PAN) for spinning, without soaking treatment, and then pre-oxidation and carbonization treatment; Co / CNFs are samples prepared by adding cobalt acetate and polyacrylonitrile (PAN) during the electrospinning process, without soaking treatment, and then pre-oxidation and carbonization treatment; Co@CNP / CNFs are electrospinning by adding cobalt acetate and polyacrylonitrile (PAN) during electrospinning, and soaking treatment, the soaking solution is only 2-methylimidazole solution, and then pre-oxidation and carbonization treatment are performed; the preparation process of Co@CNS / CNFs is similar to that of Co@CNP / CNFs, except that 2-methylimidazole solution and hexahydrate cobalt nitrate solution are added to the soaking solution at the same time; RuCo@CNS / CNFs is similar to Co@CNS / CNF, except that ruthenium chloride solution is added to the soaking solution of RuCo@CNS / CNFs on the basis of adding 2-methylimidazole solution and hexahydrate cobalt nitrate solution. Compared with CNFs, Co / CNFs can illustrate that the addition of metal salts is beneficial to the improvement of the catalytic activity of the catalyst; compared with Co / CNFs, Co@CNP / CNFs, and Co@CNS / CNFs, it is shown that the in-situ growth of nanosheets on nanofibers is beneficial to the exposure of active sites and the improvement of catalytic activity; compared with RuCo@CNS / CNFs, Co@CNS / CNFs further illustrates that the synergistic effect of Ru and Co through alloying is beneficial to the improvement of the catalytic activity of the catalytic material. Commercial Pt / C electrodes are currently the main catalyst in the field of hydrogen evolution reaction and have excellent catalytic activity, but their stability is far from satisfactory. The stability of the catalytic material prepared by the present invention can be greatly improved compared with that. Figure 4 The third figure compares the stability of the prepared catalytic material and the Pt / C electrode. It can be clearly observed that the voltage of the Pt / C electrode dropped by 240 mV after 20 hours of testing, while the voltage of the catalytic material prepared by us only dropped by 102 mV after 100 hours of continuous testing.

[0056] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.

Claims

1. A carbon nanosheet high-efficiency hydrogen evolution catalytic material with in-situ growth of RuCo alloy nanoparticles on carbon nanofibers, characterized in that: Prepared by the following steps: Step 1: Preparation of precursor cobalt nanofibers by electrospinning: Adding cobalt acetate and polyacrylonitrile to N,N-dimethylformamide and stirring thoroughly to obtain a uniformly mixed precursor solution; then transferring the precursor solution to a syringe for electrospinning to prepare precursor cobalt nanofibers; Step 2: Soak: A 2-methylimidazole aqueous solution, a cobalt nitrate aqueous solution and a ruthenium chloride aqueous solution are prepared respectively, the precursor cobalt nanofiber is immersed in the 2-methylimidazole aqueous solution for ultrasonic treatment and then taken out, and then the 2-methylimidazole aqueous solution, the cobalt nitrate aqueous solution and the ruthenium chloride aqueous solution are mixed to obtain a mixed immersion solution, and then the ultrasonically treated precursor cobalt nanofiber is immersed in the mixed immersion solution, taken out for cleaning, and dried to obtain an in-situ growth ruthenium-doped ZIF-L nanosheet intermediate on the nanofiber; Step 3: Carbonization: The ruthenium-doped ZIF-L nanosheet intermediate in situ grown on the nanofibers prepared above is first pre-oxidized in a constant temperature forced air drying oven, and then placed in a tubular furnace for calcination. Argon is introduced as a protective gas during the heating process, and finally an efficient hydrogen evolution catalytic material of carbon nanosheets loaded with RuCo alloy nanoparticles in situ grown on carbon nanofibers is obtained.

2. The preparation method according to claim 1, characterized in that: In step 1, the raw material ratio of the precursor solution is: 1-3 mM cobalt acetate, 1-3 g polyacrylonitrile, and 10-15 mL N,N-dimethylformamide.

3. The preparation method according to claim 1, characterized in that: In step 1, the electrospinning parameters were: temperature of 30 ± 5 °C, voltage of 20-25 KV, flow rate of 0.5-0.7 mL / h, and the distance between the needle and the receiver was 15-20 cm.

4. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the 2-methylimidazole aqueous solution is 0.3-0.5 mmoL / mL, the concentration of the cobalt nitrate aqueous solution is 0.05-0.1 mmoL / mL, and the concentration of the ruthenium chloride aqueous solution is 0.1-0.2 mmoL / mL.

5. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of 2-methylimidazole: cobalt nitrate: ruthenium chloride is 32:4:

1.

6. The preparation method according to claim 1, characterized in that: In step 2, the precursor cobalt nanofibers are immersed in the mixed immersion solution for 30-90 minutes.

7. The preparation method according to claim 1, characterized in that: In step three, the pre-oxidation temperature is controlled at 200±50°C and the time is controlled at 3-5 hours.

8. The preparation method according to claim 1, characterized in that: In step three, the calcination process is divided into three stages: the first stage: heating from room temperature to 300±50℃, the heating rate is 4-6℃ / min, and the insulation time is 1-3 minutes; the second stage: heating from 300±50℃ to 900±100℃, the heating rate is 4-6℃ / min, and the insulation time is 2-3 hours; the third stage: naturally cooling to room temperature.

Citation Information

Cited By

  • Boron-doped carbon nanofiber loaded ruthenium metal nanoparticle HER catalyst and preparation method and application thereof

    CN121321031A